The Analysis of Smile Component of Upper Lip Curvature of Balinese Students In The Faculty of Dentistry, Universitas Mahasaraswati Denpasar - Ketut Virtika Ayu; Wiwekowati; Norman Hidajah; Eko Sri Yuni Astuti; Gusti Agung Ayu Dimitria Aprilia Prabandika Putri (Interdental Jurnal Kedokteran Gigi (IJKG), 2025)
Introduction: Aesthetics in dentistry is increasingly becoming a major concern for patients and is often used as the main reason for dental care. One of the goals of orthodontic treatment is to obtain optimal facial aesthetics. Facial aesthetics are closely related to an attractive smile. The purpose of this study was to describe and analyze the curvature of the upper lip in Balinese at the Faculty of Dentistry, Universitas Mahasaraswati Denpasar. Materials and Methods: This research was a descriptive study with analytically processed research data. The research design was cross-sectional, using a sample of 115 students from the Faculty of Dentistry, Universitas Mahasaraswati Denpasar as subjects. The sampling technique used was purposive sampling based on inclusion and exclusion criteria. Subjects were photographed in a social smile pose, and the resulting photos were edited using a computer program to see the shape of the curvature of the upper lip. Results: The results showed that the average curvature of the upper lip was 51.3% upper direction, 20% straight, and 28.7% lower direction. Discussion: The curvature of the upper lip is influenced by the movement of facial muscles such as orbicularis oris, levator labii superioris, levator anguli oris, and zygomaticus major. Smile aesthetics are not only achieved by dentofacial improvements, but also accompanied by facial muscles that play an important role in facial aesthetics. Conclusion: The upward curvature of the upper lip was the most commonly found, followed by the downward and the straight curvature. There was no significant difference between males and females in the upper lip curvature in the Faculty of Dentistry, Universitas Mahasaraswati Denpasar students.